Family-based Early Intervention for Expressive Language Skills of Children with Hearing Impairments - Azzahra, Qori A’ina; Rochyadi, Endang; Sunardi, Sunardi (Journal of ICSAR, 2024)
The purpose of this study is early to formulate a hypothetical program of family-based early intervention that’s considered feasible and expected to be effective improving expressive language skills in children with hearing impairments. The study used a qualitative approach with family research subjects of deaf children aged 6 years who still have residual hearing and domiciled in Bandung. Data collection techniques are carried out through observation, interviews, and documentation studies. Based on the results of empirical analysis of abilities, obstacles, needs of children, and efforts that have been made by the family and its results, and based on the results of theoretical analysis based on ecological theory of family roles and responsibilities, the program focuses on the application of intensive verbal communication in daily pragmatic life by all family members. In order for the program to be implemented properly by families, the principles of consistency, imitation, and attachment, as well as the application of transfer of knowledge and transfer of skills procedures are an important part of the implementation of this program.